2018
DOI: 10.1080/13597566.2018.1473857
|View full text |Cite
|
Sign up to set email alerts
|

Towards a scholarship on regional elections

Abstract: This introduction article inaugurates the first annual special issue on regional elections which sets out to nurture a community of regional election scholars who seek to understand the factors driving regional voters, regional election outcomes, and regional electoral dynamics across the globe. This is a much-needed research effort given that the territorial scope and importance of regional elections have increased considerably over the past four decades yet most scholarship remains focused on national electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Comparative regional-level data on public opinion, elites, social movements, and political parties are now available for much of the developed world (e.g. Schakel and Romanova 2018;Tatham and Bauer 2016;Zuber and Szöcsik 2019). Commensurate data would be immensely valuable for a wider range of regions.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative regional-level data on public opinion, elites, social movements, and political parties are now available for much of the developed world (e.g. Schakel and Romanova 2018;Tatham and Bauer 2016;Zuber and Szöcsik 2019). Commensurate data would be immensely valuable for a wider range of regions.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the provincial elections are in line with their second-order nature (cf. Schakel and Romanova 2018). Only one of four coalition parties, the ChristenUnie, managed to gain votes, the other three lost.…”
Section: Vote Choice and Election Resultsmentioning
confidence: 99%
“…In this scenario, regional voters use the European election to signal their discontent with parties in regional government and, as a result, these parties lose vote share whereas parties in regional opposition (and small and new parties) gain vote share. There is ample of (recent) evidence that some voters conceive regional elections equally or more important than national elections (e.g., Bechtel, 2012; Golder et al, 2017; Schakel & Romanova, 2018; Scully, 2013) and a number of authors have found that turnout in regional contests is often higher than for European elections (e.g., Henderson & McEwen, 2015; Rallings & Trasher, 2005; Schakel & Dandoy, 2014). Therefore, it can be expected that many voters think that regional elections are more important than European elections.…”
Section: Theorizing Regional Spillover Into European Electionsmentioning
confidence: 99%